2017
DOI: 10.1002/jmri.25804
|View full text |Cite
|
Sign up to set email alerts
|

Spatial fuzzy c‐means thresholding for semiautomated calculation of percentage lung ventilated volume from hyperpolarized gas and 1H MRI

Abstract: Purpose: To develop an image-processing pipeline for semiautomated (SA) and reproducible analysis of hyperpolarized gas lung ventilation and proton anatomical magnetic resonance imaging (MRI) scan pairs. To compare results from the software for total lung volume (TLV), ventilated volume (VV), and percentage lung ventilated volume (%VV) calculation to the current manual "basic" method and a K-means segmentation method. Materials and Methods: Six patients were imaged with hyperpolarized 3 He and same-breath lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 19 publications
(73 reference statements)
1
47
0
Order By: Relevance
“…While improving the reproducibility and the calculation of %VV through the benefits of obtaining 1 H and 129 Xe images inherently coregistered in the same breath hold, CS also has a negligible influence on the derived %VV values. The mean absolute difference of 1.3% in global %VV found between prospective FS and CS datasets is below the previously calculated mean interobserver error in %VV calculation (2.3%) when analyzing FS images with the same software . It is also within the same‐day reproducibility confidence interval of %VV measurement (±1.52%) previously reported in Ebner et al Our results are in line with Qing et al, who previously reported that CS was a good candidate to accelerate the acquisition of 3 He ventilation and 1 H images in the same breath without compromising image fidelity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While improving the reproducibility and the calculation of %VV through the benefits of obtaining 1 H and 129 Xe images inherently coregistered in the same breath hold, CS also has a negligible influence on the derived %VV values. The mean absolute difference of 1.3% in global %VV found between prospective FS and CS datasets is below the previously calculated mean interobserver error in %VV calculation (2.3%) when analyzing FS images with the same software . It is also within the same‐day reproducibility confidence interval of %VV measurement (±1.52%) previously reported in Ebner et al Our results are in line with Qing et al, who previously reported that CS was a good candidate to accelerate the acquisition of 3 He ventilation and 1 H images in the same breath without compromising image fidelity.…”
Section: Discussionsupporting
confidence: 90%
“…H score is then defined as the mean value of the distribution of H i,j,k . Finally, %VV was also calculated for each AF and for the fully sampled DICOM images using a semiautomated segmentation software …”
Section: Methodsmentioning
confidence: 99%
“…Medical image segmentation software (Mimics; Materialise, Leuven, Belgium) was used to segment the lungs of the inspiratory and expiratory CT scans. 3 He and 1 H MR lung parenchyma were segmented in Matlab (MathWorks, Natick, MA) using a modified version of the Spatial Fuzzy Cmeans (FCM) algorithm presented by Chuang et al (2006) as recently described (Hughes et al, 2017). Prior to segmentation, images were pre-processed using a bilateral filter (Tomasi and Manduchi, 1998).…”
Section: Image Segmentationmentioning
confidence: 99%
“…Ventilation defects are clusters of voxels that represent ventilatory slow space. They can be identified through at least three different methods: manually by an experienced observer, through hierarchical k-means clustering (18), or by spatial fuzzy c-means clustering (15).The lung elements in our study that are designated as constricted certainly include voxels that would be designated as ventilation defect, but they also include others that strongly respond to methacholine, as indicated by their Ͼ50% drop in FEV1 but not to the point that they would be considered "defects." For example, a lung element with a relatively high SV (say of 0.3 compared with a lungwide mean SV of 0.2) that fell to an SV of 0.14 (compared with a lungwide mean SV of 0.2) would be considered constricted but would probably not be considered to be part of a defect.…”
Section: Sv Heterogeneitymentioning
confidence: 99%